Numerical investigation of perforated aluminum tubes with different types of geometrical discontinuities under bending - Karakaya, Cetin; Ekşi, Seçil (International Journal of Computational and Experimental Science and Engineering, 2025)
In this study, the effect of hole shape on the bending behavior of aluminum 6063-T5 tubes was investigated numerically. The effects of hole geometries in the form of circles, triangles, squares, hexagons, ellipses, and diamonds on the bending behavior of the tube structure were investigated by finite element analysis. As a result of the analysis, the tube structure with the highest load-carrying and energy-absorption capacity is the ellipse perforated tube. In terms of specific load carrying and specific energy absorption capacity, the ellipse perforated tube structure is again in first place. Compared to the non-perforated tube, the load carrying capacity has decreased by 13.6%, and the energy absorption capacity has decreased by 11%. The triangular perforated structure comes in second place. The square perforated tube is in last place.